Improving the Welfare of Border Communities: The Mediating Role of Good Governance on the Relation between Intellectual Capital and Social Capital - Arthana, I Komang; Nursiani, Ni Putu; Riwu, Yonas Ferdinand (Nurture, 2025)
Purpose: This study aims to identify the role of good governance in mediating the relationship between the influence of intellectual capital and social capital toward improving the welfare of people in border villages. Design/Methodology/Approach: The methodology used in this study is quantitative, with data collection by online questionnaires and analysis using Partial Least Square (PLS). Findings: Good governance mediates the relationship between intellectual capital’s influence and full mediation’s characteristics. Good governance also mediates the relationship between social capital’s influence and partial mediation’s characteristics. Conclusion: This study concludes that the values and sanctions contained in good governance encourage village financial managers to follow the rules and policies that, have been set. In addition, social capital embedded in border village communities shows that village fund management based on customary values strongly influences community welfare. Research Limitations/Implications: This study may be limited to data taken from specific villages in the Belu Regency, which may lead to difficulties in generalizing these findings to other border villages that may have different social, economic, or political contexts. Practical Implications: The importance of strengthening good governance in managing village funds, as well as the need to consider customary values in managing resources to improve the welfare of communities in border villages. Contribution to the Literature: The study provides new insights into the role of good governance in mediating the relationship between intellectual capital and social capital, and its impact on community welfare in the context of border villages.